Peran Lembaga Penjamin Simpanan Dalam Penanganan Bank Gagal dan Strategi Pencegahan Krisis Keuangan di Indonesia - Mahesa Arya Pratama; Yosua Parulian Pardede; Jesika Bonita Sibarani; Intan Gloria Mawar Silangit (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The banking industry has a crucial role in maintaining the balance of development and economic integrity of a country. Banks act as depositories and distributors of liquidity funds which are essential for the sustainability of economic activities. To carry out this function effectively, strict regulations and supervision are needed. As well as guaranteeing customer deposits to ensure healthy and sustainable bank operations. The financial crisis that occurred in 1997 in Indonesia showed structural weaknesses in the banking system, including ineffective supervision and weak bank management. The government responded with a Banking Guarantee program (Blanket Guarenteen), but this program faced various problems and was not continued. As a solution, the Deposit Insurance Corporation (LPS) was formed through Law Number 24 of 2004, which aims to increase public confidence in the banking system and maintain financial system stability. This research aims to analyze the role of LPS in dealing with failed banks and the effectiveness of banking regulations in preventing future financial crises. The results of the analysis are expected to provide policy recommendations to strengthen the stability of the banking system.